Electronic Government 11th IFIP WG 8.5 International Conference, EGOV 2012, Kristiansand, Norway, September 3-6, 2012. Proceedings - Scholl, Hans J.; Janssen, Marijn; Wimmer, Maria A.; Moe, Carl Erik.; Flak, Leif Skiftenes; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 11th IFIP WG 8.5 International Conference, EGOV 2012, held in Delft, The Netherlands, in September 2012. The 23 revised full papers presented were carefully reviewed and selected from more then 80 submissions. The papers are organized in topical sections on foundations; adoption and diffusion; open government and transformation; infrastructure and technology; evaluation; and citizen perspective, social inclusion, and social media.
Foundations -- Adoption and Diffiusion -- Open Government and Transformation -- Infrastructure and Technology -- Evaluation -- Citizen Perspective, Social Inclusion, and Social Media.
Keywords: Computer science; Information storage and retrieval systems; Information systems; Computers -- Law and legislation; Information Systems; Computer Science; Legal Aspects of Computing; Computer Appl. in Administrative Data Processing; Computers and Society; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems